The use of misoprostol in cervical ripening and induction of labour in the term pregnancy - Smith, Patricia Anne (Department of Obstetrics and Gynaecology, 2017)
OBJECTIVE: To compare the efficacy and safety of misoprostol (Cytotec) with prostaglandin E2 (prandin gel) in cervical ripening and induction of labour at term. STUDY DESIGN: Two independent studies were performed. The first was to evaluate misoprostol as a cervical ripening agent when compared to prandin gel and the second to compare their ability to induce labour. Two hundred and forty patients requiring cervical ripening prior to induction of labour were recruited to the cervical ripening arm of the trial. Patients were randomly assigned to receive either 100 μg of misoprostol (half a 200 μg tablet) in the posterior fornix or 1mg prandin gel similarly inserted. A Bishop's score of the cervix was performed prior to drug insertion and repeated by the same clinician 24 hours thereafter if labour or delivery had not ensued. If labour commenced it were managed according to standard labour ward protocols. Three hundred and forty patients who required induction of labour for maternal or fetal reasons at term were recruited to the induction of labour arm of the trial. Half were randomly allocated to receive 100 μg misoprostol (half a 200 μg tablet) in the posterior fornix and half, 1mg prandin gel in the posterior fornix. If after 4 hours the labour had not ensued or the cervix remained too unfavourable for amniotomy, then a second dose of the drug was used. Labour and delivery was managed according to standard labour ward protocols. RESULTS: In the cervical ripening trial, data was analysed on 113 patients in the misoprostol arm and 116 in the prandin arm. The demographic characteristics were similar in both groups. Significantly more patients delivered within the 24-hour ripening period with misoprostol (88 (77.9%)) than with prandin gel (47 (40.5%)) (P < 0.001). In those patients delivered within 24 hours, the induction of labour to delivery interval was similar at, 9 hours 30 minutes (SD = 5h30) for misoprostol and 10 hours 51 minutes (SD = 5h09), with prandin gel. Significantly more patients in the prandin gel arm required oxytocin augmentation (25.5% versus 12.5% with misoprostol) but the caesarean section rate (13.6% with misoprostol and 12.7% with prandin gel) and analgesic usage were similar. Maternal side effects were similar in the two groups but tachysystole was significantly more common at 12.4% with misoprostol and 1.7% with prandin gel (P<0.01). In those patients undelivered at 24 hours, there was a significant improvement in the number of patients with a Bishop's score of > 4 with both drugs. Neonatal outcomes, including Apgar score and admission to the neonatal intensive care unit were not significantly different. In the induction of labour arm of the trial the demographic characteristics of both groups were similar. The use of misoprostol resulted in a significantly higher number of patients delivering within 12 hours of drug insertion than with prandin gel (136 (80%) with misoprostol versus 91 (66,9%) with prandin gel, P < 0.001). There was also a significantly shorter insertion to delivery interval with misoprostol (9hr13 (SD = 5hr 53)) than with prandin gel (12hr18 (SD = 6h22)), (P < 0.001). Thirty nine patients in the misoprostol group required a second dose of the drug versus 55 patients in the prandin gel group (P<0.05). Although the caesarean section rate was similar with the two drugs (30.6% with misoprostol and 34.1 % with prandin gel) significantly more patients had a caesarean section for fetal distress in the misoprostol group (21.8% vs 10.6%) (P < 0.05). Neonatal outcome, as assessed by Apgar score and admission to the neonatal intensive care unit, was however not different with either drug. Four patients had abruptio placentae in the misoprostol group and the incidence of tachysystole was significantly higher at 28.2% vs 15.3% with prandin gel (P< 0.01). Oxytocin was used for labour augmentation in 52.9% of patients with prandin gel and 27% with misoprostol (P < 0.05). Analgesic usage and other maternal side effects were similar with both drugs. CONCLUSION: Misoprostol is an effective cervical ripening and induction of labour agent when compared to prandin gel. However, it results in a higher incidence of tachysystole, caesarean section for fetal distress and abruption placentae and cannot yet be recommended for general use until the concern over adverse fetal and maternal outcome is addressed in larger trials.